FRI0550 Differential impact of obesity, structural severity and their combination on the efficacy of viscosupplementation in patients with knee osteoarthritis. post-hoc analysis of a double-blind, controlled, multicenter, randomised trial. (12th June 2018) - Conrozier, T.; Eymard, F.; Chevalier, X.; Balblanc, J.-C.
Abstract : Background: It has been demonstrated that radiological severity and obesity were independent factors of VS failure and that the percentage of patients fulfilling the OMERACT-OARSI response criteria was only 41.7% in patients with both marked joint space narrowing and obesity while it was 87.1% in those who did not have any of these two risk factors. 1 Objectives: The aim of the study was to assess the impact of obesity, radiographic severity and their combination on pain and function scores, 6 months after viscosupplementation in patients with knee osteoarthritis. Methods: Post-hoc analysis of a prospective, double-blind, randomised, multicentre, parallel-group trial, aimed to compare 2 viscosupplements (x 3 weekly intra articular injections of HANOX-M or Bio-HA) in patients with symptomatic knee OA. Patients were classified according to body mass index (BMI<or≥30 kg. -2 ) and to OARSI radiological grade (1–2 versus 3). Responses in terms of WOMAC pain and function scores (differences between baseline and 6 months, as well as their variation over time) were compared according to BMI, radiological grade and to the combination of the 2 parameters. Results: One-hundred and sixty-six patients from the intent-to-treat population, were analysed: Forty-seven patients (28.3%) were classified as obese (BMI ≥30 kg. -2 ). At baseline WOMAC pain score was similar in obese and non-obese patients, whereas WOMAC function score was statistically higher in obese versus non-obese subjects. At month 6, WOMAC pain and function scores decreased significantly by 43.4% and 41.9% (p<0.0001). At month 6, WOMAC pain was significantly lower in non-obese than in obese patients (4.9±4.1 versus 7.1±4.9; p=0, 008) and in patients OARSI grade 1–2 versus 3 (4.8±4.3 versus 6.4±4.5; p=0.009). WOMAC pain score, was 85, 7% greater in obese/grade 3 patients than in non-obese/grade1–2 subjects (7, 8±5.1 versus 4, 2±4.1, p=0.001). Lastly, the decrease of pain was twice greater in non-obese patients with OARSI 1–2 than that of obese patients with OARSI grade 3 (-5.7±4.3 versus −2, 8±4.3, p=0.007). Similarly, WOMAC function score at month 6 was significantly higher in obese versus non-obese patients, in OARSI 3 versus OARSI 1–2 and in obese/grade 3 than in non-obese/grade 1–2. Conclusions: This trial confirms that obesity and advanced stage are independent predictors of a lower response to viscosupplementation in knee OA. We identified a population sub-group (patients with both obesity and severe joint space narrowing) for who HA should not be recommended, regarding the weak benefit it provides. Reference: [1] Eymard F, Chevalier X, Conrozier T. Obesity and radiological severity are associated with viscosupplementation failure in patients with knee osteoarthritis. J Orthop Res2017. doi:10.1002/jor.23529 Acknowledgements: The authors acknowledge LABRHA SAS for having allowed them to use the study database Disclosure of Interest: T. Conrozier Consultant for: LABRHA SAS, Speakers bureau: LABRHA SAS, F. EYMARD: None declared, X. CHEVALIER: None declared, J.-C. BALBLANC: None declared